2018
DOI: 10.1101/344911
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structures of the heart specific SERCA2a Ca2+-ATPase

Abstract: The sarcoplasmic/endoplasmic reticulum Ca2+‐ATPase 2a (SERCA2a) performs active reuptake of cytoplasmic Ca2+ and is a major regulator of cardiac muscle contractility. Dysfunction or dysregulation of SERCA2a is associated with heart failure, while restoring its function is considered as a therapeutic strategy to restore cardiac performance. However, its structure has not yet been determined. Based on native, active protein purified from pig ventricular muscle, we present the first crystal structures of SERCA2a,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 76 publications
(63 reference statements)
1
21
0
Order By: Relevance
“…The previous crystallographic studies of SERCA1a demonstrated that during the transition from the E1∙2Ca 2+ -ATP to E2P states, the nucleotide-binding site in the N domain and the Ca 2+ exit channel constituted by TM4 to TM6 are opened to the cytosolic and luminal sides, respectively, to facilitate the release of adenosine 5′-diphosphate (ADP) and Ca 2+ ( 5 , 13 ). Similar conformational changes were observed for recently reported crystal structures of SERCA2a in E1∙2Ca 2+ -AMPPCP and cyclopiazonic acid (CPA)–stabilized E2-AlF 4 − states ( 11 , 14 ). The present study revealed that, similarly to SERCA1a and SERCA2a, AMPPCP binds to the boundary of the P and N domains of SERCA2b, resulting in a compact headpiece cluster composed of the cytosolic A, N, and P domains ( Fig.…”
Section: Resultssupporting
confidence: 88%
“…The previous crystallographic studies of SERCA1a demonstrated that during the transition from the E1∙2Ca 2+ -ATP to E2P states, the nucleotide-binding site in the N domain and the Ca 2+ exit channel constituted by TM4 to TM6 are opened to the cytosolic and luminal sides, respectively, to facilitate the release of adenosine 5′-diphosphate (ADP) and Ca 2+ ( 5 , 13 ). Similar conformational changes were observed for recently reported crystal structures of SERCA2a in E1∙2Ca 2+ -AMPPCP and cyclopiazonic acid (CPA)–stabilized E2-AlF 4 − states ( 11 , 14 ). The present study revealed that, similarly to SERCA1a and SERCA2a, AMPPCP binds to the boundary of the P and N domains of SERCA2b, resulting in a compact headpiece cluster composed of the cytosolic A, N, and P domains ( Fig.…”
Section: Resultssupporting
confidence: 88%
“…T897 is located within the ER membrane and unlikely to be accessible to cytoplasmic OGT (Horakova, 2013;Vangheluwe, 2005). T358 is located near a Ca 2+ binding pocket, based on a recent crystal structure of SERCA2a in a pig heart (6HXB; Sitsel et al, 2019), making any potential O-GlcNAcylation event well positioned to regulate SERCA2 function through Ca 2+ binding. The other putative O-GlcNAcylated residue, T648, is a known phosphorylation site (Zhao et al, 2011) and thus a likely target for functionally relevant post-translational regulation of the protein.…”
Section: Islet O-glcnacylation In Response To Obesitymentioning
confidence: 99%
“…This mutation is known to induce phosphorylation overshoot caused by accumulation of dephosphoenzyme at steady state [55], so this crystal structure probably serves as a model to describe specific structural transitions occurring along the E1-to-E2 transition. Other structures of SERCA, such as 6hxb [56], may also help identify the structure of SERCA intermediates along the catalytic cycle of the pump, but conclusions drawn from this structural information should be interpreted with caution, especially if the information suffers from low resolution.…”
Section: Phosphorylation and Actuator Domainsmentioning
confidence: 99%